2001
DOI: 10.1021/jp010808l
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Dynamics of Organic Radical Ions in Liquids and in Low-Temperature Matrices

Abstract: The excited-state dynamics of the radical cations of perylene (PE •+ ), tetracene (TE •+ ), and thianthrene (TH •+ ), as well as the radical anions of anthraquinone (AQ •-) and tetracenequinone (TQ •-), formed by γ irradiation in low-temperature matrices (PE •+ , TH •+ , AQ •-, and TQ •-) or by oxidation in sulfuric acid (PE •+ , TE •+ , and TH •+ ) have been investigated using ultrafast pump-probe spectroscopy. The longest ground-state recovery time measured was 100 ps. The excited-state lifetime of PE •+ is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 62 publications
5
87
0
4
Order By: Relevance
“…There is, however, no spectroscopic evidence for the formation of such an excited Pe •+ */TCNE •− product. Transient spectra measured after the excitation of Pe •+ at 532 nm in sulfuric acid show that Pe •+ * does not absorb significantly between 470 and 750 nm [80]. Moreover, ground state recovery measurements of Pe •+ after excitation at 532 nm indicate an excited state lifetime of 3 ps [81].…”
Section: Looking For the Normal Region For Crmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, however, no spectroscopic evidence for the formation of such an excited Pe •+ */TCNE •− product. Transient spectra measured after the excitation of Pe •+ at 532 nm in sulfuric acid show that Pe •+ * does not absorb significantly between 470 and 750 nm [80]. Moreover, ground state recovery measurements of Pe •+ after excitation at 532 nm indicate an excited state lifetime of 3 ps [81].…”
Section: Looking For the Normal Region For Crmentioning
confidence: 99%
“…Indeed, only a very small number of radical ions are known to fluoresce [80,[92][93][94][95][96][97]. Moreover, the very few investigations on their excited state dynamics have shown that the ground state recovery of radical ions is ultrafast and takes place in picosecond timescale [80,81,98,99]. This result, together with a relatively small oscillator strength for the D 0 -D 1 transition of many radical ions, can explain this lack of fluorescence, which moreover should often occur in the near IR region.…”
Section: Electronically Excited Cs Product?mentioning
confidence: 99%
“…However, their excited-state properties are still mostly unknown. [3] Only a very few of them have been reported to fluoresce, [4][5][6] making the detection of electronically excited radical ions extremely difficult. The lack of emission is usually explained by a very efficient internal conversion favored by a small energy gap between the first electronic excited state (D 1 ) and the ground state (D 0 ), and/or by the presence of D 2 / D 1 and D 1 /D 0 conical intersections (CI).…”
mentioning
confidence: 99%
“…All the radical ions that we have studied so far are characterised by very short excited-state lifetimes, ranging from ~100 fs to a few ps, and by weak excited-state absorption features. [20][21][22][23] Therefore, if excited radical ions are formed in a bimolecular CS, their detection is extremely difficult. Substantial efforts in this direction are being invested.…”
Section: Some Old Problemsmentioning
confidence: 99%